Design, development and evaluation of a Telemonitoring System for Heart Failure patients - Yanicelli, Lucía María (2020)
Objective: Heart Failure (HF) is a chronic and lifestyle-related disease that affects patient’s quality of life. In the last years, telemonitoring systems (TSs) have been promoted as a strategy for HF management. However, the distinctive requirements that a TS should have, have not been clearly identified. To this aim, the most relevant requirements for telemonitoring of HF patients are derived from evidence-based Clinical Practice Guidelines (CPGs). The main objective of this work is to design, develop and evaluate a TS for HF patients, named SiTe iC, using widely accepted CPGs. Methods: CPGs were thoroughly reviewed to pinpoint key functional requirements of TSs. Interviews with HF patients and specialist physicians in HF were performed to design the system. Results: The functional requirements of TSs for HF patients were established. A TS (SiTe iC) was designed and programmed. The system was thoroughly assessed through a clinical trial that demonstrates that telemonitoring using SiTe iC actually improves patient’s self-care when compared to usual care and it has the potential to avoid HF re-hospitalizations. Conclusions: This study demonstrated that the identified functional requirements for TSs are relevant. In addition, thanks to SiTe iC, HF patients took an active role in their disease management.